Foreign Office, political and other departments, general correspondence before 1906, Persia (FO 60) (PRO, 1972)
Contains selections from the 734 volumes of dispatches, reports, and correspondence relating to Persia, created or inherited by the British Foreign Office (reference no. FO 60) between the years 1807 and 1905. The records constitute part of Public Record Office group Foreign Office class 60 (PRO FO 60)